2020
DOI: 10.1371/journal.pone.0238414
|View full text |Cite
|
Sign up to set email alerts
|

Social media as a tool for scientific updating at the time of COVID pandemic: Results from a national survey in Italy

Abstract: In the face of the rapid evolution of the COVID-19 pandemic, healthcare professionals on the frontline are in urgent need of frequent updates in the accomplishment of their practice. Hence, clinicians started to search for prompt, valid information on sources that are parallel to academic journals. Aim of this work is to investigate the extent of this phenomenon. We administered an anonymous online cross-sectional survey to 645 Italian clinicians. Target of the survey were all medical figures potentially invol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 11 publications
2
13
0
2
Order By: Relevance
“…Scientific literature seemed to be disproportionately consulted by biologists, doctors, pharmacists and nurses, in line with the data that emerged from the literature, as all these professionals require continuous updating on epidemiology and disease management guidelines [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Scientific literature seemed to be disproportionately consulted by biologists, doctors, pharmacists and nurses, in line with the data that emerged from the literature, as all these professionals require continuous updating on epidemiology and disease management guidelines [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…This seems to differ somehow from literature with focus on physicians' or pharmacists' uses of social media. Studies reported that most physicians increased their use of social media during the pandemic, with social media being the most important source of COVID-19 information [65,66]. In addition, pharmacists used and actively encouraged their colleagues to use social media [67].…”
Section: Discussionmentioning
confidence: 99%
“…However, the information may be inaccurate and unreliable. Therefore, it is critical to monitor and reduce its adverse psychological and social effects on people, which can help them manage the pandemic better within communities [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%